Effect of Encapsulation of Boron Nanoparticles Using Reduced Graphene Oxide on their Oxidation Characteristics. Issue 8 (27th April 2021) - Zhang, Hongyi; Du, Xinyi; Li, Gang
Abstract: Boron is a well‐known high‐energy solid. A thick oxide coating on the particle, however, inhibits its ignition and reduces its energy significantly. In this work, graphene nanosheets were used as a protective material for encapsulating boron nanoparticles (NPs) to prevent their oxidation from the air at room temperature. Boron‐reduced graphene oxide (RGO) composites were prepared under hydrothermal conditions using graphene oxide (GO) and commercial or washed boron NPs as precursors. Boron‐RGO composites were characterized using X‐ray diffraction (XRD), transmission electron microscopy (TEM), Raman spectroscopy, X‐ray photoelectron spectroscopy (XPS), thermogravimetry (TG), and differential scanning calorimetry (DSC). XPS data show that no boron oxide or boric acid was present on the surface of washed boron particles and boron‐RGO composites. It seems that the removal of boron oxide or boric acid layer on the commercial boron particle surface and the reduction of graphene oxide occurred simultaneously during hydrothermal treatment. XRD data show that boric acid re‐formed on washed boron NPs but not on the boron‐RGO composites after these two samples had been exposed to ambient temperature air for four months. This indicates that the anti‐oxidation stability of boron against air at room temperature was improved greatly after encapsulation of reduced graphene oxide. The heat of combustion of boron‐RGO composites (46.6∼49.3 kJ ⋅ g −1 ) measured by oxygen bomb calorimetry was higher than that of the commercial boron NPs (43.4 kJ ⋅ g −1 ). Upon heating, the boron‐RGO composite begins oxidizing at a lower temperature than the commercial boron particles. A mechanism was proposed for encapsulation of boron NPs with RGO. Abstract :